2022
DOI: 10.1371/journal.pntd.0011017
|View full text |Cite
|
Sign up to set email alerts
|

Extensive diversity of RNA viruses in ticks revealed by metagenomics in northeastern China

Abstract: Background Ticks act as important vectors of infectious agents, and several emerging tick-borne viruses have recently been identified to be associated with human diseases in northeastern China. However, little is known about the tick virome in northeastern China. Methods Ticks collected from April 2020 to July 2021 were pooled for metagenomic analysis to investigate the virome diversity in northeastern China. Results In total, 22 RNA viruses were identified, including four each in the Nairoviridae and Phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…SGLV was also found in local Ixodes crenulatus, Ixodes persulcatus, Haemaphysalis concinna, and H. longicornis . Subsequently, some researchers annotated the sequence of SGLV in the metagenomic sequencing of ticks from northeastern China ( Liu et al, 2022 ; Cai et al, 2023 ; Ji et al, 2023 ). Beiji nairovirus (BJNV), also a new nairo-like virus, was first mentioned in high-throughput sequencing, and then it was detected in a febrile patient in Inner Mongolia Province.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLV was also found in local Ixodes crenulatus, Ixodes persulcatus, Haemaphysalis concinna, and H. longicornis . Subsequently, some researchers annotated the sequence of SGLV in the metagenomic sequencing of ticks from northeastern China ( Liu et al, 2022 ; Cai et al, 2023 ; Ji et al, 2023 ). Beiji nairovirus (BJNV), also a new nairo-like virus, was first mentioned in high-throughput sequencing, and then it was detected in a febrile patient in Inner Mongolia Province.…”
Section: Resultsmentioning
confidence: 99%
“…Beiji nairovirus (BJNV), also a new nairo-like virus, was first mentioned in high-throughput sequencing, and then it was detected in a febrile patient in Inner Mongolia Province. Researchers identified BJNV infections in several tick-bitten patients in Heilongjiang and Jilin Provinces, and BJNV was also detected in local ticks, including I. persulcatus, I. crenulatus, Demacentor silvarum, D. nuttalli, H. concinna and H. longicornis ( Wang YC et al, 2021 ; Liu et al, 2022 ). Yezo virus (YEZV) is a new Orthonairovirus first detected in Japan in 2019 and is currently only reported in Japan and China ( Kodama et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…While differences were identified in the I. persulcatus virome among different regions, no apparent distinction was found for viruses with the potential to infect humans. Although previous metagenomic studies have explored the tick-borne pathogen spectrum in the region [ 5 , 6 ], we provided a more comprehensive understanding of tick-borne virus diversity across the three regions. Alpha and beta diversity analyses revealed that Yanbian shows significantly greater diversity at the viral family and species levels compared to Baishan, and the viral spectrum composition of I. persulcatus also differs between these two regions.…”
Section: Discussionmentioning
confidence: 99%
“…Located within the transnational area of Changbai Mountain, these border cities are characterized by a temperate monsoon climate and is abundant in forests and wildlife resources. These environmental characteristics provide favorable conditions for tick proliferation and the circulation of tick-borne viruses [ 6 ]. TBEV has been prevalent in this region for a considerable time [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tick-borne diseases frequently occur and show an expanding situation which is a great threat for public health. 1 Haemaphysalis longicornis, a tick species belong to the phylum Arthropoda, order Ixodida, and superfamily Ixodoidea, is a temporary parasite on the body surface of many vertebrates. 2 Studies have shown that ticks have a wide range of hosts, including 200 species of mammals, 120 species of birds and a few reptiles.…”
Section: Introductionmentioning
confidence: 99%